Translating the Untranslatable : The Problem of Translating Shifting Linguistic Gender Expressions to Finnish - Vapaavuori, Iris (My University, 2025)
This thesis examines the Finnish translations of shifting linguistic gender expressions by and about a genderfluid character in Rick Riordan’s novel The Hammer of Thor. It focuses on problems that arise from Finnish having no grammatical gender, while the gender expression in translation is constructed mainly through grammatically gendered features, such as 3rd person personal pronouns. The strategies used to translate these so-called untranslatable instances are analyzed through the framework of foreignization, domestication and queer modes of translation to evaluate how the different problems were solved and what issues remain. The thesis concludes that only translating gender as far as Finnish language norms allow is not just domesticating but also risks effacement and foreignization of the gender identity itself. This calls for more care and creativity to be put into translating transgender texts and identities.
Keywords: literary translation, queer translation, gender, transgender, untranslatability, personal pronouns